O liberalismo de princípios aplicado à judicialização dos direitos sociais fundamentais: uma proposta para a superação de limites de atuação do poder judiciário - PAES, Carolina Bastos Lima (Universidade Federal do Pará, 2017)
The 1988 Constitution of the Federative Republic of Brazil has enshrined the dignity of the human person as one of its fundamentals, and has brought forth a vast amount of fundamental rights and guarantees to be applied and implemented by the State, with maximum priority, as instruments for the fostering of this fundamental principle. Among the constitutionally guaranteed rights to the individual, are the fundamental social rights, which aim to provide basic material conditions to all individuals in order for them to draw up and pursue, in a free and conscious way, their individual life plan. However, the practical implementation of those economical and social rights has not sufficiently met the demands set by the human dignity principle, neither through legislative and administrative means nor in judicial seat. This happens because, more often than not, the existence of the social rights, if not their enjoyment, remain conditioned to the availability of enough public resources to cover the costs of its implementation. Starting from this problem, the current dissertation aims to improve the actions of the Judiciary in the exercise of its goal of guaranteeing solidity to the constitutional norms that define the fundamental social rights. Towards this end, theoretical support is found in the liberalism of principles, more specifically, in the theory of justice as equity, by John Rawls, with complement offered by the equality of resources, by Ronald Dworkin, and by equality of capabilities, by Amartya Sen, instead of the utilitarianism that guides not only the elaboration and execution of social policies, but also the judicial intervention in these policies, in the manner in which it often comes forward. The goal is to allow the diversion of the attention of the judicial authorities, until now focused on the collective well-being, towards the individual, in a way in which the limits of action of the Judiciary can be overcome, for, then, at least in this extraordinary way, the State cabe made to answer, in adequate levels, the basic needs of all individuals, in trune accomplishment of its constitutional duties.